Lubuk Larangan sebagai Etnopedagogi Pendidikan Agama Islam Berbasis Kearifan Lokal - Mustopa; Erdiyan Saputra; Mona Novita; Ansori; Endah Sri Hartati (PT Cendekia Education Center, 2026)
This study aims to examine the Lubuk Larangan tradition as an ethnopedagogical resource for Islamic Religious Education (IRE) grounded in local wisdom in Bungo Regency, Jambi Province, Indonesia. A qualitative approach with a case study design enriched by ethnographic perspectives was employed to explore the interrelationship between cultural practices, Islamic values, and community life. The research was conducted in two villages where the Lubuk Larangan tradition remains actively practiced. Ten informants, consisting of customary leaders, religious leaders, Islamic Religious Education teachers, and community members, were purposively selected. Data were collected through in-depth interviews, non-participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The trustworthiness of the findings was ensured through source and method triangulation, member checking, and thick description. The findings reveal that Lubuk Larangan embodies Islamic educational values encompassing aqidah (faith), sharia (Islamic law), and akhlaq (morality), which are internalized through communal cultural practices. The tradition fosters religious character, social responsibility, environmental stewardship, and collective ethics based on deliberation and public welfare. These findings demonstrate that Lubuk Larangan serves as a meaningful ethnopedagogical resource for developing contextual, reflective, and culturally responsive Islamic Religious Education rooted in local wisdom.